Peningkatan Pengetahuan Mahasiswa Pada Topik Neuromuskular Melalui Pendekatan Edukasi Teman Sebaya Pada Era Teknologi Kecerdasan Buatan - Arwan Bin Laeto (Yayasan Al-Afif, 2025)
The development of artificial intelligence (AI) in education raises increasingly palpable concerns, particularly regarding the potential decline in students' critical thinking skills and learning independence. Excessive use of AI in completing academic tasks can foster a dependence on technology, replacing a learning process that should shape character and deep understanding. This study aims to measure the increase in students' knowledge related to neuromuscular topics through a peer education approach. This research was used a descriptive categorical method with a cross-sectional approach, designed with a pre-test and post-test design and the t-test used to determine the significance. The results of study indicate that learning using a peer education approach related to the topic of neuromuscular can significantly improve students' knowledge (p=0.001). Learning that uses an educational approach to peers can enhance students' knowledge about neuromuscular topics, thus this innovative learning approach can be used as an alternative method of learning.